Mina - Forsythe, Matthew, 1976- (New York, New York : Simon & Schuster Books for Young Readers, an imprint of Simon & Schuster Children's Publishing Division, 2022)
Mina the mouse is very upset when her father brings home a pet "squirrel" that she is certain is a cat.
Keywords: Mice -- Juvenile fiction; Cats -- Juvenile fiction; Pets -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Humorous stories; Mice -- Fiction; Cats -- Fiction; Pets -- Fiction; Fathers and daughters -- Fiction; Humorous stories